2017
DOI: 10.1016/j.xphs.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications Associated With the Posttranslational Modification–Induced Functional Impairment of Albumin in Oxidative Stress–Related Diseases

Abstract: Recent research findings indicate that the posttranslational modification of human serum albumin (HSA) such as oxidation, glycation, truncation, dimerization, and carbamylation is related to certain types of diseases. We report herein on a simple and rapid analytical method, using an electrospray ionization time-of-flight mass spectrometry technique, that allows posttranslational modifications of HSA to be quantitatively and qualitatively evaluated with a high degree of sensitivity. In patients with chronic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 64 publications
(93 reference statements)
1
57
0
1
Order By: Relevance
“…In healthy subjects, Cys34 is mainly present in a reduced form (≈70 %) (HSA red ), whereas 25 to 30 % is reversibly oxidized (HSA ox ), as a mixed disulfide with cysteine, cysteinylglycine, homocysteine, or GSH (HSAox) . Small amounts (3–4 %) of irreversibly oxidized forms, such as sulfinate and sulfonate, are also found . Under pathologic conditions, such as kidney or liver diseases, the level of oxidized albumin may increase to up to 70 % .…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…In healthy subjects, Cys34 is mainly present in a reduced form (≈70 %) (HSA red ), whereas 25 to 30 % is reversibly oxidized (HSA ox ), as a mixed disulfide with cysteine, cysteinylglycine, homocysteine, or GSH (HSAox) . Small amounts (3–4 %) of irreversibly oxidized forms, such as sulfinate and sulfonate, are also found . Under pathologic conditions, such as kidney or liver diseases, the level of oxidized albumin may increase to up to 70 % .…”
Section: Resultsmentioning
confidence: 66%
“…HSA has 35 cysteine residues; 34 are paired in 17 robust disulfide bonds and only one, cysteine‐34 (Cys34), is readily available for SDSL . In healthy subjects, Cys34 is mainly present in a reduced form (≈70 %) (HSA red ), whereas 25 to 30 % is reversibly oxidized (HSA ox ), as a mixed disulfide with cysteine, cysteinylglycine, homocysteine, or GSH (HSAox) . Small amounts (3–4 %) of irreversibly oxidized forms, such as sulfinate and sulfonate, are also found .…”
Section: Resultsmentioning
confidence: 99%
“…oxidized albumin) before and after dialysis (0.24 mM and 0.25 mM) while Terawaki et al [15] observed large variations (from 55% to 33%, respectively). By considering that about 90% of the oxidized albumin is represented as the mixed disulfide Cys 34 S-SCys and that the average concentration of albumin is 0.7 mM [4], it results that about 0.1 mM of cysteine is released from the protein to the plasma during about 3 h of dialysis. 1A).…”
Section: Changes Of Oxidized Serum Albumin In Kidney Dialyzed Patientsmentioning
confidence: 99%
“…One curious exception is represented by Cys 34 of HSA, which is the most abundant protein in plasma, reaching the concentration of 0.6-0.8 mM [2]. In healthy subjects, this residue is mainly present in a reduced form (about 70%) (HSA red ) while 25-30% is found as a reversible oxidized form, that is, as mixed disulfide with cysteine and in minor amounts with cysteinylglycine, homocysteine, and GSH (HSA ox ) [3,4]. Cys 34 [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation